Flotation separation of smithsonite from calcite by using flaxseed gum as depressant. (15th June 2021) - Zhou, Hepeng; Yang, Zhizhao; Zhang, Yongbing; Xie, Fanxin; Luo, Xianping
Highlights: Flaxseed gum (FG) used as depressant in flotation process for the first time. The FG has excellently selective depression effect on calcite. Flotation separation of smithsonite from calcite can be achieved with FG. The chemisorption dominates the interaction of FG with calcite. Abstract: Flotation separation of smithsonite from calcite is difficult due to the complex associated relationship between smithsonite and calcite, the surface properties are similar and calcite has good natural floatability. Flaxseed gum (FG), a natural pollution-free extract, was used as a kind of selective depressant firstly for flotation of smithsonite. The all results of flotation tests indicated that the FG can significantly affected the recovery of calcite by using NaOl as collector at pH 9.5, while the recovery of smithsonite was barely affected. Meanwhile, according to the results of zeta potential analysis, XPS analysis and FTIR analysis, the interaction between FG and calcite is stronger than smithsonite due to its selective depression ability. The hydroxyl groups in FG have strong chemical reaction with Ca 2+ sites exposed on the mineral surface, which greatly affects the adsorption of NaOl on calcite surface. On contrast, the reaction strength between FG and smithsonite is significant lower, which has little effect on the interaction between NaOl and smithsonite. In conclusion, all the results of tests and analysis illustrated FG can be used as a selective depressant of calcite to separate smithsonite from calcite efficiently.